(untitled) (Revista Latino-Americana de Enfermagem, 1998)
This survey aimed at characterizing the population of pregnant women utilizing prenatal care services of a Basic Health Unit in the city of Ribeirão Preto, São Paulo, Brazil in July 1995 and analyzing the records of the service given to pregnant women who went to this Unit in terms of general and specific anamnesis, general and tocogynecological physical examination and the diagnostic procedures used in this service. The records showed a lack of information about patients´ general and specific anamnesis, general and tocogynecological physical examination and clinical condition, characterizing a more ritualistic procedure. Therefore, records did not meet the objectives proposed by the Program for Comprehensive Women Health Care of the Ribeirão Preto City Health Department with the São Paulo State Health Department and the Health Ministry: to ensure good quality in women's care service regarding their clinical, gynecological, obstetric and mental needs; to identify, prevent, and control risk factors which may affect women's health; to diagnose and treat women's pathologies as soon as possible, among others.